Resistência de união de dois sistemas adesivos universais à dentina afetada de dentes decíduos - Rodrigues, Andressa (2024)
This laboratory study was conducted to compare the bond strength of the Scotchbond Universal Plus (3M Oral Care) adhesive system with its predecessor system, Scotchbond Universal (3M Oral Care), to affected dentin of primary teeth. Twenty sound primary molars were prepared and randomized into 4 experimental groups (n=5) according to adhesive system - Scotchbond Universal Plus (SBU Plus) and Scotchbond Universal (SBU) and application strategy - acid etching or self-etching. The adhesive systems were applied to the dentin surfaces previously demineralized by pH cycling according to the manufacturer's recommendations, and then flow composite resin cylinders (Opallis Flow; FGM) were obtained by filling starch tubes (internal diameter 0.96 mm and height 1 mm). Three to four resin cylinders (specimens) were obtained from each tooth. The specimens were stored in distilled water in an oven at 37°C for twentyfour hours and then evaluated under a stereomicroscope to verify the possible need for replacement due to bubbles or failures. After the microshear test, the specimens were observed under a stereomicroscope to determine the failure mode, which was classified as adhesive/mixed or cohesive failure. The MPa data were subjected to a two-way analysis of variance (ANOVA) to compare the mean bond strength values of the main factors (adhesive system and application strategy) and the interaction between the factors. Statistical analyses were performed using the Jamovi software (version 2.5) at a 5% significance level. ANOVA indicated that there was no significant effect for the factors adhesive system (F = 0.05; p = 0.83) and application strategy (F = 0.98; p = 0.34), nor for the interaction (F = 0.01; p = 0.96). Therefore, no significant differences were observed between adhesive systems with respect to etching strategy. Failures were classified as adhesive/mixed and no cohesive failures were observed. Based on the results obtained and considering the limitations of this laboratory study, it can be concluded that SBU Plus has similar bond strength to its predecessor when applied to affected dentin of primary teeth, contradicting the manufacturer's claim of immediate superiority. Furthermore, the acid etching strategy does not affect the bond strength of the adhesive systems considered.